Vitamin D and T- regulator cells are not independent factors for RDS in premature neonates - Putri Maharani Tristanita Marsubrin; Agus Firmansyah; Rinawati Rohsiswatmo; Yuditiya Purwosunu; Zakiudin Munasir; Tetty Yuniati (Paediatrica Indonesiana, 2021)
Background The high morbidity and mortality of premature neonates remain significant problem in Indonesia with respiratory distress syndrome (RDS) as one of the most common problem. Vitamin D plays an important role in lung maturity. Vitamin D deficiency causes epithelial cell inflammation, leading to a higher risk of RDS. Previous studies suggest that T regulatory cells (Treg) in inflammatory diseases, such as RDS in neonates, are possibly linked to vitamin D deficiency. Objective To determine the role of vitamin D on RDS and Treg cells in very premature or very low birth weight neonates. Methods A prospective cohort study conducted on premature neonates in Neonatology Division, Department of Child Health, Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Umbilical cord blood samples were collected to evaluate total vitamin D 25-OH levels and Treg cells. Subjects with RDS were evaluated until the end of the observation period. Results The mean umbilical cord vitamin D level was 15.79 (SD 6.9) ng/mL, and 53% of the subjects were found to be deficient. As much as 65.1% of neonates had RDS. The mean Treg level was 11.38 (SD 2.45)%. No significant correlation was observed between vitamin D level and the occurrence of RDS (RR 0.87; 95%CI 0.56 to 1.34; P=0.53); vitamin D level and the dysregulation of Treg cells (RR 1.30; 95%CI 0.76 to 2.21; P=0.31) as well as between Treg dysregulation and RDS (RR 1.11; 95%CI 0.70 to 1.75; P=0.64). However, we found that RDS group had a lower gestational age and higher presentation of dysregulation Treg. Conclusion In very premature or very low birth weight neonates, no association between occurence of RDS and vitamin D deficiency as well as Treg cell dysregulation.